To the Question of Optimization of the Process of Mechanical Activation of Metallurgical Slag - Adilkhodzhaev, Anvar Ishanovich; Kadirov, Ilkhom Abdullayevich; Kudratov, Bekzod Sherzodovich (European Journal of Life Safety and Stability (2660-9630), 2022)
As you know, mineral additives in the concrete mix compositions have become an almost indispensable component that can significantly improve the physical and technical performance of concrete. In comparison with other types of additives, they have the greatest impact on the corrected formation of the structure and properties of the designed concrete while simultaneously saving cement.